Search for W ' boson resonances decaying to a top quark and a bottom quark - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Sonnenschein, L.; et al. (Amer Physical Soc, 2008)
We search for the production of a heavy W ' gauge boson that decays to third generation quarks in 0: 9 fb(-1) of p (p) over bar collisions at root s = 1: 96 TeV, collected with the D0 detector at the Fermilab Tevatron collider. We find no significant excess in the final-state invariant mass distribution and set upper limits on the production cross section times branching fraction. For a left-handed W ' boson with SM couplings, we set a lower mass limit of 731 GeV. For right-handed W ' bosons, we set lower mass limits of 739 GeV if the W ' boson decays to both leptons and quarks and 768 GeV if the W ' boson decays only to quarks. We also set limits on the coupling of the W ' boson to fermions as a function of its mass.